1990
DOI: 10.1269/jrr.31.256
|View full text |Cite
|
Sign up to set email alerts
|

Acquired radioresistance after low dose X-irradiation in mice.

Abstract: Low doses (2.5-15 cGy) of X-irradiation two months prior to a second exposure to a sublethal dose enhanced the survival rate in mice. Optimal and significant increase was observed with 5-10 cGy. Endogenous spleen colony counts (endo-CFUs) after 7 Gy increased by a factor of about 1.7 in mice pre-irradiated with 5-10 cGy, while the number of blood forming stem cells (CFUs) in the pre-irradiated group did not exceed that in the sham-irradiated control group at the period of the second exposure (two months after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 6 publications
1
34
0
Order By: Relevance
“…Increased intracellular glutathione participates in the protective mechanisms against radiation, one effect of which is to increase oxidative stress. 6,8) Cellular levels of GSH are influenced by multiple factors, including the activities of enzymes in the g-glutamyl cycle, the availability of precursors such as cysteine, and the rate of consumption or efflux of GSH. In this case, the elevation of intracellular GSH seems to be mediated by signal transduction pathways which participate in the regulation of glutathione biosynthesis-related molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased intracellular glutathione participates in the protective mechanisms against radiation, one effect of which is to increase oxidative stress. 6,8) Cellular levels of GSH are influenced by multiple factors, including the activities of enzymes in the g-glutamyl cycle, the availability of precursors such as cysteine, and the rate of consumption or efflux of GSH. In this case, the elevation of intracellular GSH seems to be mediated by signal transduction pathways which participate in the regulation of glutathione biosynthesis-related molecules.…”
Section: Discussionmentioning
confidence: 99%
“…3) Several kinds of effects of low-dose radiation on living organisms have been recognized; these include stimulation of the growth rate, 4) tumor progression, 5) activation of immune function, 6) suppression of reactive oxygen species (ROS)-related diseases, 7) resistance to high-dose irradiation, 8) and prolongation of life span. 9) However, the mechanisms underlying these responses remain obscure.…”
mentioning
confidence: 99%
“…These effects, called "radiation hormesis", include stimulation of growth rate (Luckey 1982), enhancement of survival after lethal high-dose of irradiation (Yonezawa et al 1990), prolongation of life span (Ducoff 1975) and elevation of resistance to oxygen toxicity (Lee & Ducoff 1984). Numerous articles also demonstrated "beneficial" effects of the low-dose irradiation on immune system in humans and animals (Safwat 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Since the editio princeps of the AR concept introduced into radiation biology (Olivieri et al, 1984), this phenomenon has been demonstrated both in vitro and in vivo (Takahashi & Ohnishi, 2009;Mitchel, 2006;Vares et al, 2006). Though studies on the radiation-induced radioresistance in rodents in vivo could be retrospected to the later 1940s (Dacquisto, 1959), the first full-dress investigation on AR in mice started about 50 years later by Yonezawa and colleagues (Yonezawa et al, 1990). In a series of comprehensive studies, a variety of experimental condition combinations of the priming and challenging doses, the interval between the irradiations, and the mouse strain were testified and verified (Yonezawa, 2006), laying a cornerstone of in vivo model for AR in mice -successful establishment of the mouse models for AR induction by acute low liner energy transfer (LET) X-irradiations at the whole body level using survival from bone marrow death as the main endpoint, which is the so-called "Yonezawa Effect" in Japan (Takahashi & Ohnishi, 2009).…”
Section: Introductionmentioning
confidence: 99%